An active post-marketing surveillance study to evaluate the safety and immunogenicity of Zyvac TCV in healthy participants - Sanjay Vasant Mankar; Chintan Patel; Abhishek Chavan; Ravi Modi; Lisa Sarangi; Virendra Nath Tripathi; Dillip Kumar Dash; Jai Prakash Narayan; Sunil Bandgar; N. Ravi Kumar; Vinay Kumar Gill; Munish Kumar Kakkar; et al. (Human Vaccines & Immunotherapeutics)
Typhoid fever remains a significant public health concern in endemic regions, with increasing antimicrobial resistance heightening the need for preventive strategies such as vaccination. Zyvac-TCV, a typhoid conjugate vaccine developed by Zydus Lifesciences Ltd. is licensed for use across all age groups. This prospective, multicenter, single-arm post-marketing surveillance study evaluated the safety and immunogenicity of Zyvac TCV in 3037 healthy participants aged 6 months to 45 years, enrolled across multiple Indian centers. Each participant received a single 0.5 mL intramuscular dose. Safety was assessed through monitoring of adverse events (AEs) over a 6-month period, while immunogenicity was evaluated in a subset of 300 participants by measuring serum anti-Vi IgG antibody titers at baseline and Day 28 post-vaccination. Overall, 16.7% of participants reported AEs, predominantly mild or moderate in nature, with no serious adverse events. Immunogenicity results demonstrated a seroconversion rate of 94.7% and a significant increase in geometric mean titers from 4.5 U/mL at baseline to 1787.8 U/mL at Day 28. A post-hoc batch analysis showed consistent immunogenicity across three commercial vaccine batches. Zyvac TCV was well tolerated and elicited a strong immune response in all age groups, supporting its integration into national immunization programs in typhoid-endemic regions.